Management of Zakat Funds through the Z-Chicken Program in Community Welfare at BAZNAS Trenggalek Regency - Qoni'ah, Diwani Fatati; Siswahyudianto, Siswahyudianto; Supriyadi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research was conducted because of this program which is an empowerment program to improve community welfare in BAZNAS Trenggalek Regency. This research uses a qualitative approach with descriptive research type. Data collection techniques through observation, interviews and documentation. Interviews were conducted with informants including BAZNAS Trenggalek Regency staff, program assistants and also mustahik recipients of Z-Chicken Program assistance. The results of this research show that BAZNAS Trenggalek Regency's way of improving the welfare of the community through the Z-Chicken program takes the form of an empowerment program, the results of which the program can help improve the welfare of the Trenggalek community. There are even some mustahik who have succeeded in becoming muzakki. Evaluation of the Z-Chicken program at BAZNAS Trenggalek Regency was carried out on the policy content, namely that the program was quite successful in achieving its goal, namely improving the economy and welfare of the Trenggalek community. Evaluation of program implementation is more focused on selecting mustahik recipients of Z-Chicken program assistance. Meanwhile, evaluation of the impact is more focused on increasing the positive impact and trying to reduce or eliminate the negative impact.